The F domain of estrogen receptor α is involved in species-specific, tamoxifen-mediated transactivation - Arao, Yukitomo (J Biol Chem, 2018)
Estrogen receptor α (ERα) is a major transducer of estrogen-mediated physiological signals. ERα is a member of the nuclear receptor superfamily, which encompasses ligand-dependent transcription factors. The C terminus of nuclear receptors, termed the F domain, is the least homologous region among the members of this family. The ERα F domain possesses 45 amino acids; however, its function remains unclear. We noticed that the homology of the F domains between mouse and human ERαs is remarkably lower (75.6% similarity) than that between the entire proteins (94.7% similarity). To assess the functionality of the ERα F domains, here we generated chimeric ERα expression constructs with mouse-human–exchanged F domains. Using cell-based in vitro assays, we analyzed the transcriptional coactivator interaction and ligand-binding domain dimerization activities of these mouse–human F domain–swapped ERαs. We found that the transcriptional activity of the mouse WT ERα is more potent than that of the human WT ERα in the human hepatoma cell line HepG2. 4-Hydroxytamoxifen (4OHT)-mediated transcriptional activity of mouse–human F domain–swapped ERαs was the inverse of the WT ERα activities but not estradiol-mediated transcriptional activities. Further experiments with constructs containing deletion or point mutations of a predicted β-strand region within the F domain suggested that this region governs the species-specific 4OHT-mediated transcriptional activity of ERα. We conclude that the ERα F domain has a species-specific function in 4OHT-mediated receptor transactivation and that mouse–human F domain–swapped ERα mutants enable key insights into ERα F domain structure and function.